Effects of GLP-1 receptor agonists on kidney and cardiovascular disease outcomes: a meta-analysis of randomised controlled trials - Badve, Sunil V.; Bilal, Anika; Lee, Matthew M.Y.; Sattar, Naveed; Gerstein, Hertzel C.; Ruff, Christian T.; McMurray, John J.V.; Rossing, Peter; Bakris, George; Mahaffey, Kenneth W.; Mann, Johannes F.E.; Colhoun, Helen M.; et al. (Lancet Diabetes and Endocrinology, 2025)
Background: GLP-1 receptor agonists reduce the risk of major adverse cardiovascular events (MACE) and can also have kidney benefits. However, whether GLP-1 receptor agonists improve clinically important kidney outcomes remains uncertain. We aimed to comprehensively assess the effects of GLP-1 receptor agonists on kidney and cardiovascular disease outcomes by performing a meta-analysis of randomised controlled trials. Methods: For this meta-analysis, we searched MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials for randomised controlled trials that included at least 500 participants with type 2 diabetes, compared a GLP-1 receptor agonist with placebo with at least 12 months of follow-up, and reported a primary clinical kidney or cardiovascular outcome, from database inception to March 26, 2024. Post hoc, we included the SELECT trial (NCT03574597), which enrolled participants with cardiovascular disease and a BMI of 27 kg/m2 or more without diabetes. Study-level summary data were extracted independently by two authors for inclusion in this random-effects analysis. The main kidney outcome was a composite outcome, consisting of kidney failure (kidney replacement therapy or a persistent estimated glomerular filtration rate [eGFR] <15 mL/min per 1·73 m2), a sustained reduction in eGFR by at least 50% or the nearest equivalent, or death from kidney failure. The main cardiovascular outcome was MACE, consisting of cardiovascular death, non-fatal myocardial infarction, or non-fatal stroke. This study is registered with PROSPERO, CRD42024528864. Findings: Of the 5140 records identified through the literature search, 11 trials, involving 85 373 participants (29 386 female, 55 987 male), were included in the meta-analysis. In participants with type 2 diabetes (67 769), GLP-1 receptor agonists reduced the composite kidney outcome by 18% compared with placebo (hazard ratio [HR] 0·82, 95% CI 0·73–0·93; I2 =26·41%), kidney failure by 16% (HR 0·84, 0·72–0·99; I2 =0%), MACE by 13% (HR 0·87, 0·81–0·93; I2 =49·75%), and all-cause death by 12% (HR 0·88, 0·83–0·93; I2 =0%). The effect on the composite kidney outcome (HR 0·81, 95% CI 0·72–0·92; I2 =23·11%), kidney failure (HR 0·84, 0·72–0·98; I2 =0%), MACE (HR 0·86, 0·80–0·92; I2 =48·9%), and all-cause death (HR 0·87, 0·82–0·91; I2 =0%) was similar when the SELECT trial was included, with no evidence of heterogeneity between this trial and those including participants with type 2 diabetes (pheterogeneity >0·05). There was no difference in the risk of serious adverse events, including acute pancreatitis and severe hypoglycaemia, between the GLP-1 receptor agonist and placebo groups (risk ratio [RR] 0·95, 95% CI 0·90–1·01; I2 =88·5%). However, treatment discontinuation due to adverse events occurred more frequently in the GLP-1 receptor agonist groups (RR 1·51, 95% CI 1·18–1·94; I2 =96·3%). Interpretation: We found evidence that GLP-1 receptor agonists significantly reduce clinically important kidney events, kidney failure, and cardiovascular events. Funding: None.
CRIS-Team Scopus Importer:2025-02-17